Pengembangan Panduan Konseling Realitas Untuk Meningkatkan Tanggung Jawab Belajar Siswa di SMK Negeri 5 Bulukumba - Pada, A. Indi Tenri; Saman, Abdul; Latif, Suciani (Universitas Negeri Makassar, 2025)
This research aims to develop a reality counseling guide to increase students' learning responsibility at SMK Negeri 5 Bulukumba. . The research method used Research and Development (R&D) with the Borg and Gall model modified into seven stages: initial research, planning, product development, internal testing, revision, field trial, and final product. The research subjects were counseling teachers and grade XI students, with data collected through questionnaires and interviews. The results showed material validity with scores of 83.3% and 95%, as well as media validity with scores of 80% and 93%. Practicality was rated very good, with a score of 84.3% by the counseling teacher and 87% from the small group trial. Based on these results, the reality counseling guide is declared feasible for use in the guidance and counseling process at SMK Negeri 5 Bulukumba.